Magnetic Resonance Imaging Techniques for Brown Adipose Tissue Detection - Wu, Mingming; Junker, Daniela; Branca, Rosa Tamara; Karampinos, Dimitrios C. (Frontiers in Endocrinology, 2020)
Magnetic resonance imaging (MRI) and magnetic resonance spectroscopy (MRS) methods can non-invasively assess brown adipose tissue (BAT) structure and function. Recently, MRI and MRS have been proposed as a means to differentiate BAT from white adipose tissue (WAT) and to extract morphological and functional information on BAT inaccessible by other means. Specifically, proton MR (1H) techniques, such as proton density fat fraction mapping, diffusion imaging, and intermolecular multiple quantum coherence imaging, have been employed to access BAT microstructure; MR thermometry, relaxometry, and MRI and MRS with 31P, 2H, 13C, and 129Xe have shown to provide complementary information on BAT function. The purpose of the present review is to provide a comprehensive overview of MR imaging and spectroscopy techniques used to detect BAT in rodents and in humans. The present work discusses common challenges of current methods and provides an outlook on possible future directions of using MRI and MRS in BAT studies.